ESRD QIP Payment Reductions Are Associated with Mortality, Utilization, and Cost. (20th August 2020) - Young, E.; Ding, Z.; Kapke, A.; Houseal, D.; Pearson, J.; Turenne, M.
Abstract : Research Objective: CMS launched the ESRD Quality Incentive Program (QIP) in 2010. The ESRD QIP adjusts Medicare payments to dialysis facilities based on their performance on a set of quality measures. The measures are revised in most years. We assessed whether the magnitude of ESRD QIP payment reductions was associated with several important patient outcomes that are not an intrinsic part of the QIP measure set. Study Design: We compared mortality, utilization of health care services, and Medicare payments per patient‐year during 2015‐2017 for dialysis facilities in each ESRD QIP payment reduction category (0%, 0.5%, 1.0%, 1.5%, and 2.0%) corresponding to their QIP performance for the same year. The data sources include Medicare claims and enrollment files. Results were expressed as unadjusted averages and as modeled measures of association that adjusted for important patient factors (age, sex, race, ethnicity, diabetes, duration of ESRD, and dual eligibility). Population Studied: The patient cohort consisted of Medicare fee‐for‐service beneficiaries receiving chronic dialysis for ESRD on the first day of each year. Patients were attributed to the first facility that provided treatment during the year. Principal Findings: Most patients were treated in facilities that did not receive an ESRD QIP payment reduction (Table). There was a stepwise increase in mortality, hospitalization, hospital days, and Medicare payments per year in facilities with successively larger payment reductions. The increase in Medicare payments was largely for inpatient services. All findings were statistically significant in adjusted regression models (shown in the Table for mortality and total payment). Conclusions: Mortality, utilization, and Medicare payments were substantially higher for patients treated in facilities whose contemporaneous performance on ESRD QIP measures resulted in a payment reduction. Moreover, these outcome measures increased stepwise with the magnitude of facility payment reductions. The findings are consistent with the hypothesis that the ESRD QIP measures and scoring system capture meaningful determinants of health care quality and value. Implications for Policy or Practice: The findings support the validity of ESRD QIP. The findings offer an approach to ongoing monitoring and validation of QIP measures. Primary Funding Source: The study was funded by the Centers for Medicare and Medicaid Services.